Antibiofilm Activity of Heather and Manuka Honeys and Antivirulence Potential of Some of Their Constituents on the DsbA1 Enzyme of Pseudomonas aeruginosa - Oscar Shirlaw; Zara Billah; Baraa Attar; Lisa Hughes; Rana M. Qasaymeh; Veronique Seidel; Georgios Efthimiou (MDPI AG, 2020)
Heather honey was tested for its effect on the formation of biofilms by Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli, Klebsiella pneumoniae, Enterococcus faecalis, Salmonella Enteriditis and Acinetobacter baumanii in comparison with Manuka honey. At 0.25 mg/mL, Heather honey inhibited biofilm formation in S. aureus, A. baumanii, E. coli, S. Enteriditis and P. aeruginosa, but promoted the growth of E. faecalis and K. pneumoniae biofilms. Manuka honey inhibited biofilm formation in K. pneumoniae, E. faecalis, and S. Enteriditis, A. baumanii, E. coli and P. aeruginosa, but promoted S. aureus biofilm formation. Molecular docking with Autodock Vina was performed to calculate the predictive binding affinities and ligand efficiencies of Manuka and Heather honey constituents for PaDsbA1, the main enzyme controlling the correct folding of virulence proteins in Pseudomonas aeruginosa. A number of constituents, including benzoic acid and methylglyoxal, present in Heather and/or Manuka honey, revealed high ligand efficiencies for the target enzyme. This helps support, to some extent, the decrease in P. aeruginosa biofilm formation observed for such honeys.